Theoretical Principles of Improving the Innovative Learning Environment in Teachers of Technology (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the improvement of the innovative educational environment for technology teachers, the activation of the knowledge, skills and qualifications of teachers, technological competence, the formation of the technological potential of students, the use of modern pedagogical technologies in the educational process based on the competence approach implementation, use of information and communication technologies in the course of the lesson, raising the level of knowledge and potential of students through the development of the teacher's pedagogical competence